Acid regulates inflammatory response in a rat model of induction of gastric ulcer recurrence by interleukin 1β. Issue 6 (1st June 2001) - Watanabe, T; Higuchi, K; Tominaga, K; Fujiwara, Y; Arakawa, T
Abstract : BACKGROUND: In a previous study we showed that interleukin 1β (IL-1β) caused recurrence of gastric ulcers in rats, and that adhesion molecules (intercellular adhesion molecule 1 and leucocytic β2 integrins) play a role in this recurrence. Although gastric acid plays an important role in many types of gastric injuries, including peptic ulcer recurrence, the mechanism(s) remains unclear. AIMS: To examine the involvement of gastric acid in induction of ulcer recurrence by IL-1β, and to investigate the role of gastric acid in inflammatory responses during ulcer recurrence. METHODS: Rats with healed ulcers were used. Rats were given 1 μg/kg IL-1β intraperitoneally. Another group of rats was given 20 mg/kg omeprazole for three days to inhibit acid secretion, and received IL-1β 20 hours after the first administration of omeprazole. They were then given 0.15 N HCl or vehicle at 0, 12, 24, and 36 hours after IL-1β treatment. Some rats were given acid alone at the same time points. Expression of adhesion molecules was examined immunohistochemically and concentrations of IL-1β and tumour necrosis factor α (TNF-α) were measured by ELISA in scar tissue 24 hours after IL-1β treatment. RESULTS: IL-1β increased expression of adhesion molecules and concentrations of IL-1β and TNF-α in scar tissue by 24 hours after IL-1β treatment, and nine of 11 healed ulcers had recurred by 48 hours. Omeprazole inhibited the effects of IL-1β. HCl acid abolished the inhibitory effects of omeprazole. Acid alone affected neither expression of adhesion molecules nor cytokine concentrations, and did not cause recurrence. CONCLUSIONS: Gastric acid is required for recurrence of gastric ulcers caused by IL-1β, and gastric acid stimulates the inflammatory process in scarred mucosa during ulcer recurrence.